Alkylverdazyls as a Source of Alkyl Radicals for Light-Triggered Cancer Cell Death - Votkina D. E. Darjya Evgenjevna; Plotnikov E. V. Evgeny Vladimirovich; Petunin P. V. Pavel Vasilievich; Berdinskaya E. S. Elizaveta Sergeevna; Tretyakova M. S. Maria Sergeevna; Audran G. Gerard; Marque S. R. A. Sylvain; Postnikov P. S. Pavel Sergeevich (2022, 2022)
Title screen